PENGARUH PENGGUNAAN CHATGPT DALAM PENULISAN LAPORAN PENELITIAN SISWA KELAS XI SMAN 1 BARRU - Risna, Risna; Azis, Abdul; Usman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe students' research report writing skills before and after using ChatGPT as an academic reviewer, and to test the statistical and practical significance of its effect. A quantitative approach with a quasi-experimental one-group pretest-posttest design was employed. Thirty-six Grade XI.F3 students of SMAN 1 Barru were selected through purposive sampling. The instrument was a five-aspect rubric (structure & organization, content & argumentation, academic language, technical aspects, and originality & academic integrity; maximum score 60), validated through expert judgment and demonstrating excellent inter-rater reliability (ICC pretest = 0.930; ICC posttest = 0.910). At the posttest stage, students completed three sequential steps: independently rewriting a research report, submitting it to ChatGPT for academic-reviewer feedback, and then independently revising based on those recommendations. Data were analyzed using descriptive statistics, Shapiro-Wilk normality test, Paired Samples T-Test, and Cohen's d effect size. Mean scores improved from 79.0 (SD = 4.76) at pretest to 90.4 (SD = 3.0) at posttest. The Paired Samples T-Test yielded t (35) = −13, p = 0.000, rejecting H₀. Cohen's d = 2.76 indicated a very large effect. The greatest gains were in Content & Argumentation (+2.8 points) and Technical Aspects (+1.8 points), while the smallest gain was in Originality & Academic Integrity (+0.4 points). These findings confirm that structured ChatGPT integration with prompt-engineering training and academic-ethics reinforcement significantly enhances high school students' research report writing quality.